PENGARUH SUPLEMENTASI DAUN UBI KAYU TERHADAP FERMENTABILITAS DAN KECERNAAN IN VITRO RANSUM BERPAKAN SERAT SAWIT HASIL AMONIASI DENGAN UREA - Mardiati Zain, Elihasridas dan Djumali Mangunwidjaja (Jurnal Teknologi Industri Pertanian, 2005)
ABSTRACTRuminant production is impeded by lack of forage and roughage.  This experiment tried to make use the ample supply of palm press fiber (PPF) as the  sources of roughage. The first experiment was conducted  to evaluate effect of urea for ammoniation on digestibility and fermentability of PPF, on the level of 2, 4 and 6% urea, respectively. The result of trial 1 indicated that digestibility and fermentability of ammoniated PPF was higher than that of  the control.  The best digestibility and fermentability was attainable by ammoniation with 6% urea.  This  best result was then used in trial 2 by supplementation  of  0, 5, 10, 15, and 20% cassava leaves based on dry matter feed (source of branched chain amino acids (BCAA) on syntesis of microbial protein, digestibility and fermentability. The experiment diet composed of 50% PPF and 50% concentrate. Supplementation of cassava leaves increased the digestibility, fermentability and syntesis of microbial protein. Supplementation of 15 % cassava leaves increase syntesis of  microbial protein to 30.64 mg/l/ hour. The result showed that ammoniated PPF with supplementation 15% DM cassava leaves was better in digestibility and syntesis microbial protein.Key words : cassava leaves, palm press fiber, ammoniation,  ruminant production